Poster 174: The Role of Familial Predisposition in Imaging-Confirmed Atraumatic Rotator Cuff Tears. Issue 7 (30th July 2022) - Ly, Amanda; Reddy, Yashas; Jain, Nitin; Du, Lichen; Atem, Folefac; Khazzam, Michael
Objectives: The etiology of rotator cuff tears is not completely understood. Several studies have identified age, smoking, hypercholesterolemia, diabetes, and hypertension as potential risk factors of rotator cuff tears. Limited data suggests the role of genetic and familial predisposition in the etiology of rotator cuff tears. Our objective was to assess whether there is an increased likelihood of rotator cuff tears in family members of patients with rotator cuff tears versus those without tears. This would provide evidence for whether there is a familial predisposition to rotator cuff tears. Methods: Patients presenting to a shoulder clinic with pain, stiffness, or instability were recruited in this study. Patients that completed a shoulder outcomes questionnaire, were age 18 years or older, and had an available MRI or CT arthrogram of the symptomatic shoulder were included in the study. Any individuals with acute traumatic rotator cuff tears were excluded from analysis. On the questionnaire, patients provided information on demographics, personal medical history, shoulder symptoms, and family history of rotator cuff tears. The diagnosis of rotator cuff tears was based on imaging (MRI or CT arthrogram) confirmation of a structural defect in the rotator cuff. The association between family history of rotator cuff problems and the likelihood of an imaging-confirmed rotator cuff tear diagnosis was evaluated using multivariate logistic regression, adjusting for age, sex, race and ethnicity, smoking, hypertension, diabetes, and depression. Results: In our cohort of 2, 337 patients, 52.7% (n=1, 231) of patients had an imaging-confirmed atraumatic rotator cuff tear. Among patients with tears, 18.0% (n=221) of patients reported a family history of rotator cuff issues versus 11% (n=123) in patients without tears. A family history of rotator cuff problems was significantly associated with the diagnosis of an imaging-confirmed rotator cuff tear (Odds Ratio=2.27, 95% CI = 1.72, 3.01). Increasing age (Odds Ratio=1.06, 95% CI = 1.05, 1.07) and Hispanic race and ethnicity (Odds Ratio=1.49, 95% CI = 1.06, 2.11 in Hispanic patients versus those of Non-Hispanic White ancestry) were also significantly associated with a rotator cuff tear diagnosis. Sex, smoking, hypertension, diabetes, and depression were not significantly associated with rotator cuff tears. Conclusions: Our study shows that individuals with rotator cuff tears were over two times as likely to have a family member with a rotator cuff tear as compared with patients without tears. These results support previous studies which have suggested a genetic component in the development of tendinopathies 1 .In a similar study by Assunção et al., individuals with familial history of treatment for rotator cuff tears were 3.3 times as likely to experience a cuff tear 2 . In another study by Harvie et al, siblings of patients with a full-thickness tear were 2.42 times more likely to experience a tear